HUBUNGAN ANTARA CITRA MEREK MOBIL SUZUKI DENGAN KEPUTUSAN PEMBELIAN PADA KONSUMEN DI DEALER SUMBER BARU MOBIL PURWOKERTO - Janah, Maslichah Raichatul (TALENTA, 2013)
More and more automotive companies that operate with a variety of products on offer has enabled people to make choices according to their needs and options , where the importance of the brand . Brand image  can not be built on lies information . A consumer in making a purchase decision is not denied if always pay attention to the image of a brand and its quality , but for mepertahankan and enhance the image of a brand is not easy to have great effort for each company .   This research aims to determine the relationship between Suzuki brand image with the consumer purchase decision in Purwokerto Car Dealers New Source . Subjects in this study is that consumers in the New Source Car dealer located in Navan area  totaling 70 people . The sampling technique used is incidental non-  random sampling . While the data collection instruments used were brand image scale and scale pebelian decision .   Moent product analysis results showed a correlation of r = 0.393 with p <  0.01 , indicating that there is a significant positive relationship between brand image obil Suzuki with purchasing decisions